Link of TMPRSS2 expression with tumor immunogenicity and response to immune checkpoint inhibitors in cancers - Karthikeyan Subbarayan; Helena Bieber; Chiara Massa; Felipe Adonis Escalona Rodríguez; SM Al Amin Hossain; Lisa Neuder; Wafa Wahbi; Tuula Salo; Sandy Tretbar; Ahmed Al-Samadi; Barbara Seliger (Journal of Translational Medicine)
Abstract Background SARS-CoV-2 and other viruses rely on the protease function of the TMPRSS2 protein to invade host cells. Despite cancer patients often experience poorer outcomes following SARS-CoV-2 infection, the role of TMPRSS2 in different cancer types has not yet been analyzed in detail. Therefore, the aim of the study was to determine the expression, function and clinical relevance of TMPRSS2 in tumors. Methods Publicly accessible RNA sequencing data from tumors, adjacent tissues and whole blood samples of COVID-19 patients as well as data from human tumor epithelial and endothelial cells infected with SARS-CoV-2 were analyzed for TMPRSS2 expression and correlated to the expression of immune-relevant genes and clinical parameters. In vitro models of cells transfected with TMPRSS2 (TMPRSS2high), siTMPRSS2 or mock controls (TMPRSS2low cells) were analyzed by qPCR, flow cytometry, ELISA and Western blot for the expression of immune response-relevant molecules. Co-cultures of TMPRSS2 model systems with blood peripheral mononuclear cells were employed to evaluate immune cell migration, cytotoxicity and cytokine release. Results Higher expression levels of TMPRSS2 were found in blood from patients infected with SARS-CoV-2, while TMPRSS2 expression levels significantly varied between the tumor types analyzed. TMPRSS2high tumor cells exhibit increased activity of the interferon (IFN) signal pathway accompanied by an increased expression of class I human leukocyte antigens (HLA-I) and programmed cell death ligand 1 (PD-L1) elevated interleukin 6 (IL-6) secretion and reduced NK cell-mediated cytotoxicity compared to TMPRSS2low mock controls. Treatment with a Janus kinase (JAK) 2 inhibitor or TMPRSS2-specific siRNA decreased TMPRSS2 expression. Co-cultures of the in vitro TMPRSS2 models with peripheral blood mononuclear cells in the presence of the immune checkpoint inhibitor nivolumab resulted in a significantly increased migration and infiltration of immune cells towards TMPRSS2high cells and a reduced release of the innate immunity-related cytokines CCL2 and CCL3. Conclusions This study provides novel insights into the role of TMPRSS2 in various tumor systems and the impact of SARS-CoV-2 infection on the host immunogenicity via the activation of immune-relevant pathways. These findings were linked to the efficacy of immune checkpoint inhibitor therapy, offering a potential alternative strategy to mitigate the severity of COVID-19.